Application of Polyacrylamide for Methylene Blue Removal from Aqueous Solutions - Mousavi, Hassan Zavvar; Khaligh, Aisan; Behzad, Mahdi; Rahchamani, Jalal (Journal of Applied Solution Chemistry and Modeling, 2014)
In this study the removal of methylene blue (MB) dye from aqueous solutions by polyacrylamide (PAA) as a potential adsorbent was reported. PAA was characterized using SEM and FTIR measurements. Batch adsorption experiments were performed as a function of the solution pH, contact time, solute concentration and temperature. Evaluation of the obtained data with isotherm studies indicated that the adsorption process was matched well with the Langmuir model. The maximum capacity of adsorbent for MB was 111.1 mg gâˆ’1. Kinetic studies were carried out on various kinetic models and the pseudo-second order kinetic model was fitted very well with experimental data. Moreover, the thermodynamic parameters indicated that the adsorption reaction was endothermic and spontaneous process.